Critical analysis of Suzanne Collins' Katniss Everdeen in the hunger games trilogy - Valderrama Pinilla, Mariela del Carmen (UDELAS, 2019)
The hunger Games is a science fiction trilogy written by Suzanne Collins, in which every year a boy and a girl from the districts of the country of Panam are chosen to participate and fight death in an arena for the title of winner. Katniss Everdeen is the main character who volunteers to go to the Hunger games to save her siister's life changes radically because she goes from being a normal girl to becoming the hero who will free people who were oppressed for seventy foor years. This work is an analysis of the main character through a meticulous and critical investigation. It seeks to study its evolution in a plot of tragic magnitude. The study is divided intosex parts, the first part is abour the general aspects of the work that will help me to identify the objetives to be carried out in my work, followed by the author's life and work to know her life and possible influences, as a third point there are the literary criticisms that help me to understand what other authors think about the trilogy. Followed by the theoretical framework that helped me to study the character clearly and finally the literary devices are analyzed, thus obtaining a better understanding of the character.